Penilaian Kinerja Sekolah Menengah Pertama (SMP) Dengan Pendekatan Balanced Scorecard (Kajian di SMP N 01 Bandar Sei Kijang Pelalawan) - Dian Wahyuni; Linda Hetri Suriyanti (Akuntansi & Ekonomika, 2019)
An educational institution must be managed like a corporate industry because with the enactment of the law on educational legal entities (BHP Law) by the government, management management in various fields is needed by using the Balance Scorecard approach to measure the performance of Bandar Sei Kijang Pelalawan 01 Junior High School using the following aspects: financial perspective, customer perspective, internal business processes, and learning and growth perspectives. Primary data which is a questionnaire is used to measure both the performance of the customer's perspective and the learning and growth perspective, while the secondary data is used to measure the performance of financial perspectives and internal business processes perspective. This study uses students and teachers and employees of Bandar Sei Kijang 01 Junior High School Pelalawan as respondents. The final results of this study indicate that the performance of SMPN 01 Bandar Sei Kijang Pelalawan is a very good level in general. The financial perspective performance shows a good ratio, which is still having to meet short and long-term obligations to outsiders, while the performance of the customer's perspective from 2016 to 2018 is getting better. In addition, internal business process performance shows a very good level and also the learning and growth perspective performance shows good categories. The result recommends Bandar Sei Kijang Pelalawan 01 Junior High School to (1) try to improve school performance that has a good level in the excellent category, (2) teachers and employees must improve service quality to students, and pay more attention to student learning problems, (3) head schools must be more innovative and creative in facing school problems, so the performance of Bandar Sei Kijang Pelangi 01 Public High School.